Recent Advances and the Mechanism of Astaxanthin in Ophthalmological Diseases - Ming Yang; Yanling Wang (Journal of Ophthalmology)
Astaxanthin (AST) is a naturally occurring carotenoid that has strong antioxidant, anti-inflammatory, and antiapoptosis effects and is used for the prevention of cancer. There is growing evidence that AST has multiple protective effects against various eye diseases. This article reviews the function and the potential mechanism of AST in dry eye syndrome, keratitis, cataract, diabetic retinopathy, age-related macular degeneration, high intraocular pressure, and other ocular diseases. It provides a theoretical basis for the clinical application of AST as a potential nutraceutical.